Penyelesaian Wanprestasi Perjanjian Jasa Wedding Organizer Akibat Force Majeure - Made Satria Dharmayuda; Anak Agung Sagung Laksmi Dewi; I Gusti Agung Ayu Gita Pritayanti Dinar (Jurnal Analogi Hukum, 2022)
Indonesia is a country consisting of sharing tribes, races, and cultures where each community has its own thoughts and understandings to live their lives. In carrying out his life, society is no stranger to the name of human rights where human behavior must not interfere with the rights of others and does not behave outside the norms that apply in accordance with positive laws. In relation to the positive laws that apply in Indonesia, the behavior of the people themselves has indirectly been regulated and for anyone who behaves outside the norm will definitely get sanctioned because his actions have harmed himself and others. In accordance with the positive law that applies force majeure is a disaster that can come at any time and occurs at the time of wedding activities making both parties not be able to give each other, especially the parties from the wedding. It cannot be said to be a default because every arranged event will be carried out properly if the default event does not occur and both parties can rearrange the wedding reception activities.